2019
DOI: 10.1021/acsmedchemlett.9b00161
|View full text |Cite
|
Sign up to set email alerts
|

A Bioreductive Prodrug of Cucurbitacin B Significantly Inhibits Tumor Growth in the 4T1 Xenograft Mice Model

Abstract: Cucurbitacin B (CuB), a highly cytotoxic constituent of the Cucurbitaceae plant, was identified to exhibit potent inhibitory activity against human cancer cells as well as normal cells. This disadvantage hampers the possibility of developing this compound into an anticancer drug candidate. In this work, several bioreductive prodrugs of CuB were designed to reduce toxicity to normal cells while maintaining the cytotoxic effect to cancer cells. Embedded with a bioreductive delivery and cleavable system in cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Despite its cytotoxicity in vitro, CuB had no significant impact on mouse body weights, and mice showed good tolerance to therapy without obvious signs of toxicity. These results were consistent with those observed for other cucurbitacins analogues 44 , 45 , further demonstrating its promising advantage as an effective eradication of malignant tumours. Of course, this future study can be the establishment of the ferroptosis relevant animal model to evaluate the basic parameters to gain insight into the clinical benefits of CuB in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…Despite its cytotoxicity in vitro, CuB had no significant impact on mouse body weights, and mice showed good tolerance to therapy without obvious signs of toxicity. These results were consistent with those observed for other cucurbitacins analogues 44 , 45 , further demonstrating its promising advantage as an effective eradication of malignant tumours. Of course, this future study can be the establishment of the ferroptosis relevant animal model to evaluate the basic parameters to gain insight into the clinical benefits of CuB in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…In summary, ve new triterpenoid saponin glycosides (1-5) have been isolated from T. cucumerina fruit bers, together with eleven known compounds (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) in this work. The anti-inammatory assays showed that the natural compounds 7 and 9 exhibited more potent NO inhibitory activities than those of positive references Celecoxib and aminoguanidine.…”
Section: Discussionmentioning
confidence: 85%
“…Studies on the cytotoxic activities of cucurbitacins from T. cucumerina have been reported. [11][12][13] However, the phytochemical investigation of the constituents of this plant has not much been undertaken. In the present study, we wish to report ve new triterpenoid saponin glycosides 1-5 together with eleven known compounds 6-16 [14][15][16][17][18][19][20][21][22][23][24] from the fruit bers of T. cucumerina.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, cucurbitacin B (approximately 250 µg/g) and CucD (approximately 50 µg/g) were present in the largest quantity [46]. In our study, we focused on CucD because of the cytotoxicity of cucurbitacin B and CucD, and anti-cancer effects in various cancer models have been reported in literature [65][66][67][68]. Despite the observed toxicity of both cucurbitacin B and CucD, the cell viability of endothelial cells of the pulmonary artery (CPAE) was measured after Tk extract inoculation to evaluate the safety of Tk, and Tk did not show any significant toxicity to CPAE (Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%